2019
DOI: 10.1016/j.celrep.2019.01.095
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Organ Genomic Characterization of Mucosal Field Effects Initiating Bladder Carcinogenesis

Abstract: Graphical AbstractHighlights d Field change in DNA methylation is the initiator of bladder carcinogenesis d The methylation changes suppressed immunity and dysregulated Ras-related pathways d Founder ACIN1 mutation in normal mucosa clonally expanded in progression to carcinoma d Cells with mutations of 22 genes expanded clonally with progression to carcinoma SUMMARYWe used whole-organ mapping to study the locoregional molecular changes in a human bladder containing multifocal cancer. Widespread DNA methylation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 97 publications
0
38
0
Order By: Relevance
“…Such a genetic heterogeneity has been found in the premalignant lesions in Barrett's esophagus, and has been linked to progression of breast tumors . The most detailed genetic studies of the premalignant urothelium has been done in research groups of Dyrskjøt, and Czerniak . Both groups have used multiregion sampling from whole organs to identify tumor‐associated mutations in the noncancerous epithelium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a genetic heterogeneity has been found in the premalignant lesions in Barrett's esophagus, and has been linked to progression of breast tumors . The most detailed genetic studies of the premalignant urothelium has been done in research groups of Dyrskjøt, and Czerniak . Both groups have used multiregion sampling from whole organs to identify tumor‐associated mutations in the noncancerous epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…If the site of tumor recurrence is different from that of the primary tumor, this is a manifestation of field cancerization, either due to single clone expansion or due to independent fields, that is, oligo‐clonal acquisition of tumor‐initiating capacity . Studies on the genetic heterogeneity of the premalignant field in patients with urothelial bladder cancer (UBC) have given important insights into the processes behind tumor initiation and favor a clonal origin . The shared clonal origin of nonmuscle invasive bladder cancer (NMIBC) recurrences has been repeatedly demonstrated even though tumors usually occur in different locations within the bladder .…”
Section: Introductionmentioning
confidence: 99%
“…To gain insight into the origins and dynamics of urothelial carcinoma several studies have analyzed the adjoining tumor free urothelium for genomic and gene alterations. The most detailed genetic studies of the premalignant urothelium in patients with UC has been performed by the groups of Dyrskjøt 9 , 10 and Czerniak 11 , 12 , showing that the urothelium in patients with urothelial carcinomas are replete with changes also present in the overt tumors. We instead analyzed several meta- and synchronous tumors from the same patient, as each overt tumor may be considered a clonal expansion of the underlying urothelium.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to the urothelium from a healthy bladder, the hypermethylation of ZO2, MYOD, and CDH13 were also detected in the urothelium with a normal appearance in patients with BCA, suggesting that epigenetic 'field defects' might be one of the reasons for the loss of epithelial integrity. Changes in DNA methylation comprise an early driver of cancer, and epigenetic changes involving DNA methylation might result in subsequent genome changes, which create a permissible environment for the onset and recurrence of BCA [25,26]. In an interesting study, the gene methylation pattern of secondary bladder recurrence of primary upper urinary tract cancer was tested and it was confirmed that the methylation rate of some genes increased with the increase in the number of recurrences, which might be a predictor of postoperative recurrence [27].…”
Section: Discussionmentioning
confidence: 99%